PENGARUH RELIGIOSITAS, CITRA DESTINASI, PROMOSI, DAN FASILITAS RAMAH MUSLIM TERHADAP KEPUASAN BERKUNJUNG DESTINASI HALAL DI MALANG (Studi Kasus Pada Mahasiswa Aktif FEB Unisma Angkatan 2018) - Afda Maulidiyah; Afifudin Afifudin; Hariri Hariri (El-Aswaq, 2022)
This study aims to determine the effect of Religiosity, Destination Image, Promotion, and Muslim Friendly Facilities on Satisfaction in Visiting Halal Destinations in Malang. This type of research is a quantitative survey research. In this study, the sample taken was active students of the Faculty of Economics and Business, Islamic University of Malang batch 2018 with a total of 135 people. This research uses quantitative data and methods the collection is by using a questionnaire via google form and  measured by a Likert scale. The analytical tool used is multiple linear regression analysis using SPSS. The results of the study partially show that: 1) Religiosity has a positive and significant effect on visiting satisfaction. 2) Destination image has a significant positive effect on visiting satisfaction. 3) Promotion has no positive and significant effect on visiting satisfaction. 4) Muslim friendly facilities have a positive and significant effect on visiting satisfaction.